(untitled) (Eureka Journal of Computing Science & Digital Innovation, 2026)
Robotic technologies have become an integral component of modern surgical practice, significantly improving surgical precision, visualization, dexterity, and patient safety. The effective operation of surgical robotic systems is fundamentally dependent on advanced information technology infrastructures that integrate hardware, software, data processing, artificial intelligence, and secure communication networks. This article provides a comprehensive and systematic analysis of the information technology foundations underlying robotic technologies in surgical practice. Key aspects such as system architecture, control algorithms, imaging technologies, machine learning, data management, cybersecurity, and networked communication are extensively examined. The study emphasizes the role of information technology in enabling accurate surgeon–robot interaction, real-time decision support, and continuous system reliability. By elucidating these foundational technologies, the article contributes to a deeper understanding of current robotic surgical systems and highlights future directions for innovation and clinical implementation.